2014
DOI: 10.1016/j.jpsychores.2014.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of interpersonal psychotherapy versus enhanced treatment as usual for women with co-occurring depression and pelvic pain

Abstract: ClinicalTrials.gov, NCT00895999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 56 publications
(66 reference statements)
0
20
1
1
Order By: Relevance
“…The clinical studies reported in this review were performed in different countries: USA (Poleshuck et al, 2014;Lattie et al, 2013;Nash et al, 2013;Darchuk et al, 2010;Unützer et al, 2008;Field et al, 2007); Republic of Ireland (Fullen et al, 2013); United Kingdom (McCracken, Sato & Taylor, 2013); Sweden (Taloyan, Alinaghizadeh & Löfvander, 2013;Bremander, Holmström & Bergman, 2010); Singapore (Tan et al, 2013); China (Tse, Vong & Tang, 2013); Denmark (Frich et al, 2012);…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical studies reported in this review were performed in different countries: USA (Poleshuck et al, 2014;Lattie et al, 2013;Nash et al, 2013;Darchuk et al, 2010;Unützer et al, 2008;Field et al, 2007); Republic of Ireland (Fullen et al, 2013); United Kingdom (McCracken, Sato & Taylor, 2013); Sweden (Taloyan, Alinaghizadeh & Löfvander, 2013;Bremander, Holmström & Bergman, 2010); Singapore (Tan et al, 2013); China (Tse, Vong & Tang, 2013); Denmark (Frich et al, 2012);…”
Section: Participantsmentioning
confidence: 99%
“…All participants had CP and in all the studies, some or all of them had depression. Instruments used by the studies to evaluate pain: Multidimensional Pain Inventory (Poleshuck et al, 2014;Nicholas et al, 2011;Darchuk et al, 2010); Escala numérica da dor (Fullen et al, 2013;Lattie et al, 2013;McCracken, Sato e Taylor, 2013;Tan et al, 2013;Tse, Vong e Tang, 2013); Beliefs About Pain Control Questionnaire (Fullen et al, 2013); Pain Self-efficacy Questionnaire (Nash et al, 2013;Tse, Vong e Tang, 2013;Dear et al, 2013); Escala Visual Analógica de Dor (Taloyan, Alinaghizadeh e Löfvander, 2013;Frich et al, 2012;Bremander, Holmström e Bergman, 2010;Chen e Francis, 2010;Samwel et al, 2009;Field et al, 2007); Pain Responses Self-Statements (Dear et al, 2013); Wisconsin Brief Pain Questionnaire (Dear et al, 2013); McGill Pain Questionnaire (Chen e Francis, 2010); Pain Catastrophizing Scale (Darchuk et al, 2010); Dutch version of the Pain Disability Index (Samwel et al, 2009); Pain Coping Inventory (Samwel et al, 2009); Brief Pain Questionnaire (Unützer et al, 2008).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations